The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/ncomms11169
|View full text |Cite
|
Sign up to set email alerts
|

A miR-192-EGR1-HOXB9 regulatory network controls the angiogenic switch in cancer

Abstract: A deeper mechanistic understanding of tumour angiogenesis regulation is needed to improve current anti-angiogenic therapies. Here we present evidence from systems-based miRNA analyses of large-scale patient data sets along with in vitro and in vivo experiments that miR-192 is a key regulator of angiogenesis. The potent anti-angiogenic effect of miR-192 stems from its ability to globally downregulate angiogenic pathways in cancer cells through regulation of EGR1 and HOXB9. Low miR-192 expression in human tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 56 publications
(84 reference statements)
3
80
1
1
Order By: Relevance
“…AntagomiR MiR-1307 treatment of mice with xenograft tumors resulted in a decrease in tumor size and an even further decrease in tumor size with paclitaxel treatment (66). Treatment of xenograft mouse models with miR-192-DOPC (1,2-dioleoyl-sn-glycero-3-phosphocholine) leads to inhibition of angiogenesis and tumor growth (67). MiR-551b-3p is located in a genomic region frequently amplified in high-grade serous EOC (68).…”
Section: Microrna Molecules As Therapy For Eocmentioning
confidence: 99%
“…AntagomiR MiR-1307 treatment of mice with xenograft tumors resulted in a decrease in tumor size and an even further decrease in tumor size with paclitaxel treatment (66). Treatment of xenograft mouse models with miR-192-DOPC (1,2-dioleoyl-sn-glycero-3-phosphocholine) leads to inhibition of angiogenesis and tumor growth (67). MiR-551b-3p is located in a genomic region frequently amplified in high-grade serous EOC (68).…”
Section: Microrna Molecules As Therapy For Eocmentioning
confidence: 99%
“…To identify miRs with altered expression in tumor vasculature, we isolated ECs from human tissue samples of high-grade serous ovarian cancer (n = 3) and normal ovarian tissues (n = 3) and performed nanostring analysis (7). Array results showed that 5 miRs were markedly upregulated and 7 miRs were downregulated in ovarian tumor ECs compared with normal ECs (Supplemental Table 1; supplemental material available online with this article; doi:10.1172/jci.insight.87754DS1).…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs (miRs) have been shown to play a vital role in tumor development and angiogenic processes by modulating the expression of critical angiogenesis factors (7). Deregulation of miRs has been identified in many cancer types and is closely related to tumor progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…He reported that there are a number of barriers to the delivery of miRNAs to ovarian cancer tumors, 6 including the finding that hypoxia downregulates the miRNA processing machinery including DICER. 7 Dr Sood's group has found that miR-192 is antiangiogenic 8 and is now optimizing delivery strategies including nanoparticle and thioaptamer approaches. These efforts are now in phase I clinical trials at MD Anderson.…”
Section: Antivascular Therapy and Adaptive Changes In The Tumor Micromentioning
confidence: 99%